Amber Brown wants extra credit - Danziger, Paula, 1944-2004; Ross, Tony (New York, NY : Scholastic, Inc., 1997)
Unhappy over her parents' divorce and her mother's boyfriend Max, nine-year-old Amber finds her schoolwork suffering.
710
Accelerated Reader AR
Keywords: Divorce -- Fiction; Schools -- Fiction